Association of M-Type Phospholipase A2 Receptor Deposition in Kidney Tissue with Treatment Outcomes in Patients with Idiopathic Membranous Nephropathy [Corrigendum] - Xie NQ; Zhang YL; Zheng ZL; Zheng QL; Chen RJ (Dove Medical Press, 2024)
Xie NQ, Zhang YL, Zheng ZL, Zheng QL, Chen RJ. J Inflamm Res. 2023;16:6319–6328. The authors have advised that they neglected to include a funding statement on page 6327 of the published paper. The funding statement should read as follows. FundingThis work was supported by Quanzhou Medical College research project (XYL2305). The authors apologize for this error.